PROBLEMS OF ADAPTATION OF RUSSIAN ACCOUNTING AND CONTROL AND ANALYTICAL PRACTICES TO THE CHALLENGES OF THE DIGITAL ECONOMY - A. Bodyako (Вестник университета, 2018)
The key positions of the concepts of the digital economy as phenomena of understanding the goals of management are defined. The article deals with the cause and effect basis of the problem of digital technologies the spread - one of the characteristic features of the future due to the progress in the microelectronics, information technology and telecommunications. It is concluded that the theoretical basis of the problem of updating the accounting and analytical methodology in the near future and the development of the conceptual apparatus require the solution of the following issues: increasing the degree of information reporting; the need for the formation of new terms, new concepts of information management of financial and economic activities.